Performance of crossbred and indigenous sheep under village conditions in the cool highlands of central-northern Ethiopia: growth, birth and body weights - Hassen, Y; Sölkner, Johann; Gizaw, Solomon; Baumung, R. (Elsevier, 2002)
Sheep in the cool highlands of central-northern Ethiopia (Menz) are of the meat type, have coarse wool, and are often perceived to be low in productivity. To increase their productivity, they have been upgraded with Awassi sheep. The aim of this study was to compare the performance of 37.5% Awassi x indigenous crossbreds with that of indigenous lambs in terms of birth weights, body weights and average daily gains at different stages from birth to 210 days of age. Data were collected between 1997 and 1999, and analysed by GLM procedures of SAS. The effects of farmer, season and birth year, linear regression of lambs' age, and dam postpartum body weights were significant for all traits studied. Sex variation was important, as the lambs grew older. Crossbred lambs were heavier than indigenous lambs at birth and at all ages. However, crossbred lambs were not significantly better than indigenous lambs in average daily gains. The birth weight advantage was also lost with increasing age, indicating that the milk production of ewes of the dam breed was inadequate to rear large size crossbreed lambs.